To the theoretical bases of research strategies - Pogosyan, Vardgues G. (Journal of the Belarusian State University. Sociology, 2019)
The strategies of social studies are considered through the prism of their own theoretical and philosophical foundations, within the framework of which their paradigm formation takes place. The correlation relationship between the variability of the resulting data from the normative method of obtaining knowledge about social reality has been confirmed. It is revealed that the worldview constructions bring subjectivism into the creation of theoretical constructs and set the limits of the heuristic possibilities of the applied approaches, causing a certain ideological bias of the linear pattern tendencies of the modern scientific mainstream. It was determined that the structure of social action and the polyvariancy of the choice, coupled with the unique algorithms of local societies predetermining cognitive and behavioral stereotypes, draw social research to a civilization pattern. It is recommended with the purpose of objectification of scientific research and obtaining valid data to use methodological tools that take into account local specifics in combination with the rejection of universalistic approaches in solving research problems in the study of social behavior.